Behavior Therapy in Those Who Are Addicted to Online Games - Atin Humayya; Heni Dwi Windarwati; Indah Winarni (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2022)
Adolescents addicted to online games harm their physical, psychological, and social health and require therapy. Providing therapy such as behavior therapy can help reduce online game addiction. This research aims to review articles that discuss the addictive behavior of online games and the therapy used. The method used in this study is a literature review by identifying articles from a systematic review identifying articles from four data based on ScienceDirect and PubMed in 2020. Based on the inclusion and exclusion criteria set, using the keywords behavior therapy, adolescents, and online game addiction from 2017-to 2020. We discovered 15 publications that satisfied the inclusion criteria and deserved to be considered in our examination of data-based articles. Adolescents who experience online game addiction discussed they vary in the causes, symptoms, effects, and psychotherapy given. Cognitive Behavioral Therapy (CBT), Social Skill Training (SST), and Mindfulness are all types of behavior therapy that can help kids addicted to online games. Psychotherapy can help teens addicted to internet games.